Substituição do milho por glicerina bruta para bovinos de corte em pastejo no período das águas - Socreppa, Leandro Munhoz (2014)
This dissertation was prepared based on two experiments with beef cattle supplemented under grazing Brachiaria brizantha Marandu during the rainy season. The first experiment aimed to evaluate the total replacement of corn (100%) for crude glycerin (CG) in concentrate supplement on the intake, digestibility, ruminal ammonia nitrogen, nitrogen in urine, feces and blood plasma. Five Nelore bulls were used with average initial body weight (BW) of 234.0 ± 18.29 kg. The experiment 5x5 Latin square with five animals and five replicates, evaluating the effect of concentrate supplementation (1.0 kg/animal, 30% CP) of mineral supplementation and replacement of corn for CG. The concentrated supplements contained 0, 33, 66 and 100% of CG replacing corn. The supply of concentrated supplements increased (P<0.05) the consumption of organic matter (OM), digestible organic matter (DOM), crude protein (CP) and non-fiber carbohydrates (NFC). Also, improved the digestibility of DM, OM, and CP MOD compared to animals supplemented only with mineral mixture, yet CG did not exert influence on the consumption and digestibility. There was an increase (P<0.05) in the levels of ammonia concentration of rumen fluid and nitrogen balance of the animals receiving concentrate supplementation, compared with mineral supplementation. The second experiment evaluated the effect of replacing corn by crude glycerin (CG) on the performance and average daily gain (ADG) in beef cattle kept on pasture during the rainy season. 30 animals home BW average of 238.6 ± 21.24 kg distributed in a completely randomized design. The supply of concentrated supplements increased average daily gain (ADG) and end BW compared to those receiving mineral supplementation. The increase in ADG averaged 0,200 kg per day. There was no effect of the substitution on the GMD whose earnings were 0.817; 1,042; 1.064 and 1.005, for 0, 33, 66 and 100%, respectively. The provision of 0.4% of BW concentrates supplements containing 30% improves the performance of beef cattle on pasture during the wet crude protein, can replace 100% of the corn for CG without any drop in performance of animals.